Colony size and not nest density drives reproductive output in the Common Tern Sterna hirundo. (27th November 2013) - Szostek, K. Lesley; Becker, Peter H.; Meyer, Barbara C.; Sudmann, Stefan R.; Zintl, Heribert; Robinson, Rob
<x xml:space="preserve">Abstract</x> Density is known to be an important factor in population size regulation. Several mechanisms of density limitation have been identified in colonial birds. We studied competition in Common Terns Sterna hirundo to assess whether the factor limiting reproductive output was competition for nest‐sites, which is dependent on local nest density, or density‐dependent competition for food resources, which is dependent on overall colony size using the same foraging area. We found strong associations of both colony size and nest density with reproductive output in five colonies of Common Terns in three different habitats (one marine, two freshwater). Based on detailed long‐term datasets of six separate sub‐colonies of the Banter See colony that differed in nest density, we found that reproductive success was not related to nest density but to overall colony size, possibly a result of resource depletion and food competition. We also found carry‐over effects of colony size during rearing on post‐fledging return rate. These results have important implications for the conservation management plans aimed at recovering declining populations of Common Terns.